(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3jhSa Hf eMeO GdWfjhOi GdOhTi s)
(3ChdgG (B:s
(3bGd CHh GdbGSe (B: (3bO LeYJ ai gPg GdebGdI UaGJ COhjI SgdI eCdhaI dPjPI GdWYe s
(3BNQgG (B:s
(3jDNP MH GdbWf ajOb Ydi GdbfI ddSGFdI hGdbfI GdjGHSI CLRGA ShGA , hJYed efg aJjdI hjMJed HOgf GdHGf s
(3fSNI KGfjIs
(3JHOG HGdebGdI GdKGfjI ai UaGJ GdCOhjI GdeQcHI GdeCdhaI GddPjPI GdWYe GdYWQjI GdQhGFMs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
Keywords: (3GdWHs